Autophagy inhibition enabled efficient photothermal therapy at a mild temperature. (October 2017) - Zhou, Zhengjie; Yan, Yang; Hu, Kewen; Zou, Yuan; Li, Yiwen; Ma, Rui; Zhang, Qiang; Cheng, Yiyun
Abstract: The heterogeneously-distributed hyperthermia in nanomaterial-mediated photothermal therapy commonly results in incomplete tumor eradication and serious damage of health tissue. Here, we found autophagy was activated in cancer cells underwent photothermal therapy and the inhibition of autophagy significantly enhanced the efficacy of photothermal killing of cancer cells. A formulation of chloroquine-loaded polydopamine nanoparticles was developed for sensitized photothermal cancer therapy, and the in vitro and in vivo study demonstrated that inhibition of autophagy remarkably augmented the efficacy of photothermal therapy, leading to efficient tumor suppression at a mild temperature. The regulation of autophagy provides a new route to increase the efficacy of photothermal cancer therapy.